Smart occupancy - how to avoid city expansion by high-density use of existing buildings. - Wiegand, Dietmar; Wirth, Siegfried (My University, 2018)
Smart Occupancy bezeichnet intelligente Formen des Managements der Nutzung gebauter Umwelt. Dabei wird davon ausgegangen, dass die mit einer Immobilie verbundenen klimarelevanten Emissionen, aber auch die Lebenszykluskosten nicht auf die Bruttogeschossfläche oder den Brutto-Rauminhalt einer Immobilie bezogen werden sollte, sondern auf die damit unterstützten Nutzungseinheiten.

Surveys carried out 2011 in Austria, Germany and Switzerland demonstrated, that class rooms stand empty for an average of 90 percent of the time of potential use, lecture rooms and office space for up to 95 percent. Still, they have to be financed, built, heated, cooled, maintained, refurbished and connected by roads, pipes and cables. Green Occupancy is defined as an intensive use of space over time combined with a user behavior taking into account all approptiate possibilities to reduce climate relevant emissions of the building. This idea is complimentary to the concept of Green Building. Buildings that do not incorporate intensity of use and user behavior are contradictionary to the overall target of Green Building: the mitigation of climate change by avoidance of climate relevant emissions! If companies, public authorities and individuals are in need of more space and consider spatial expansion, they should first analyse the space they already occupy and the degree of use. Optimisation of efficieny then can focus on improvements of the ecological footprint and of saving money. Both can be achieved by just changing the approach to workplace allocation over time. Very likely it is possible to meet demand completetly or at least in parts without additional office space. "Intelligent" management of space and its use over time has more than just ecological benefits. For example, it is social, because it makes education cheaper and affordable for low income households; it is economical, because it saves money; and it can promote casual meeting of people a major source for innovation. Due to these facts the authors intend to widen the approch towards Smart Occupancy.The conference contribution provides the results of a research study finished in 2017 by the Division Real Estate Development and Management at Vienna University of Technology (TU Wien) and Unternehmensberatung Wirth. In this study, a structured list of topics was discussed with real estate managers in Austria and Germany from companies with a staff of more than 500. The intention was to understand if these companies apply, or are able to implement, priciples of smart occupancy beyond mere cost reduction. The results show that Corporate Real Estate Management at the time being mostly does not consider ecological aspects of intensive use of space over time nor targetted adaption of user behavior. This also applies to Facility Management, and even for employee representatives and the management of big companies. "Intensifying of use" and "avoiding new building" do not have lobbies yet. The survey also reveals the necessities for implementation of an integral strategy for optimised use of built environment: Buildings readily to be used by different user groups with various demand, easy to realize with new objects, challenging in building stock; Organisational framework of company structures and procedures including technical feasability by housing technology and booking system; Company culture enabling shared space and shared responsibility.
Keywords: Gebäude; Gebäudebestand; Gebäudenutzung; Gebäudemanagement; Kosten-Nutzen-Rechnung; Umweltökonomische Gesamtrechnung; Flächeneinsparung; Klimaneutralität